Implementasi Mikrokontroler Sebagai Pengendali Lift Empat Lantai - Rif’an Tsaqif As Sadad , Iswanto , Jihad Anwar Sadad (Semesta Teknika, 2011)
In large multi-story buildings stairs to connect one floor with another floor. Itulization of stairs may not be efficient, as many technological advancement created lift for high rise buildings. An elevator being electronically controlled may be used to connects all floors within the building. in roder to be able to function as intended. The elevator control system prototype being produced uses a microcontroller as a controller. The microcontroller being used is the ATmega16 type. Actuator is used as a DC motor drive rotating at 300 rpm to produce a stable rotation and meet the quite large torque. This system uses a queue keystrokes. The system has functioned well and can work as expected. Lift can work in accordance with keystrokes outside and inside the elevator.